ANALISIS EKONOMI POTENSI PENGEMBANGAN INDUSTRI PERIKANAN YANG BERNILAI TAMBAH BERBASIS SUNGAI DAN DANAU DI KABUPATEN SINTANG - Evy, Marselina (Universitas Kapuas Sintang, 2025)
This research is inspiring by the significant potential of inland fisheries in Sintang Regency. In addition, Sintang Regency has shown a strong commitment to environmental conservation efforts. In fact, the local government issued the Sintang Lestari Regional Action Plan in 2019 and incorporated it into the Regional Medium-Term Development Plan (RPJMD) for the 2021–2026 period. The production levels of both capture and aquaculture fisheries in Sintang Regency are also relatively high. Currently, local fishing communities—especially those around Lake Jemut and Lake Jentawang—have begun developing processed fish products such as belonsong lais (seasoned salted fish) and salai lais (smoked fish). However, the production process remains traditional and is highly dependent on weather conditions, which results in high production costs. This study employs a mixed-methods approach, combining both qualitative and quantitative methods. The findings indicate that the belonsong lais product packaged in smaller sizes (250 grams) using vacuum plastic offers the highest added value. Similarly, salai lais in 250-gram packages provides the greatest added value. Meanwhile, toman cage culture (keramba) is only profitable when using self-produced feed. Based on these findings, it is recommended that assistance programs be provided to fish processors in Nanga Ketungau and Jentawang Hilir Villages to help them produce value-added products. In addition, capacity-building initiatives are needed for fish processors and community members interested in investing in toman fish farming in the lakes.